Interface structure between coal gangue ceramsite and cement matrix - Tianyu Han; Renliang Shan; Guoye Jing; Weiping Zhao; Zhenyu Xu; Dongjie Qiao; Haotian Wu (Case Studies in Construction Materials)
Due to the shortage of sand and gravel in the construction industry and the growing accumulation of coal gangue in the coal industry, using coal gangue ceramsite (CGC) as the coarse aggregate for concrete presents a new approach for resource utilization. This study aims to investigate the interface between CGC and cement matrix. First, the reactivity of raw coal gangue aggregate (CGAraw) and CGC was analyzed, revealing that the pozzolanic activity of the Al and Si elements in CGC was higher than that of CGAraw. CGC exhibited relatively high cylinder compressive strength compared to other lightweight aggregates. The impact of varying CGC contents on the physical, mechanical, and microstructural properties of concrete was characterized by various methods. Additionally, a modification mechanism of CGC on interface structure was determined. The result indicated that as the CGC content ranged from 0 % to 100 %, the cube compressive strength decreased by 15.04 %, the oven-dry density decreased by 18.07 %, the microhardness of the ITZ increased from 52.12 HV to 106.76 HV, and the thickness of the ITZ decreased from 47.23 μm to 17.21 μm. The activated SiO2 and Al2O3 on the surface layer of CGC reacted with calcium hydroxide during secondary hydration, producing needle-like ettringite (Aft) crystals and flocculent C-S-H gel, which enhanced the bond between the cement matrix and CGC. Considering the secondary hydration of CGC, the oven-dry density formula was modified by genetic algorithm. Additionally, coal gangue ceramsite lightweight high-strength concrete was determined as green concrete by a specific CO2 intensity index. This study could offer technical support for utilizing CGC in the high-strength concrete industry.